Trauma of the Past: The Impact of Adverse Childhood Experiences on Adult Attachment, Money Beliefs and Behaviors, and Financial Transparency - D.Bruce Ross; Ed Coambs; Emily Johnson (Journal of Financial Therapy, 2022)
Adverse childhood experiences (ACEs) can have a strong, lasting impact on our mental and relational outcomes as adults. They may also impact how we address financial beliefs and behaviors. The current study utilizes 500 participants from Amazon MTurk and structural equation modeling (SEM) to explore the relationships between ACEs and relational financial transparency behaviors through attachment style and money beliefs and behaviors. Findings indicated significant direct and indirect associations across these pathways, particularly for experiences of reported neglect, verbal, and sexual abuse on less security in adult attachment styles. In turn, insecure attachment styles were linked to increased maladaptive financial beliefs and behaviors which were significantly associated with less financial transparency in the relationship. The findings provide support for the impact of childhood trauma on inter-and intra-financial behaviors. Practice implications are discussed for financial practitioners in utilizing a narrative financial therapy modality while still adhering to ethical considerations.
Keywords: Attachment; Family finance; Adverse Childhood Experiences; Money Beliefs; Money behaviors; Trauma